Strategi Dakwah Ibu Hj. Yusi Repelitawati dalam Memberdayakan Jamaah Majelis Taklim Khoirunnisa di Lamongan - Cicik Khudaifah; Aflachal Muthowah (Academia Publication, 2021)
This study uses qualitative research conducted by the author directly to see the reality of the field directly, with the methods of observation, interviews and documentation. The author's data processing or analysis technique uses descriptive. This study uses the ACTORS theory of empowerment proposed by Sarah Cook and Stave Macaulay which is intended in this study to understand the meaning behind the actions of Mrs. Hj. Yusi Repelitawati related to the empowerment of the Khoirunnisa taklim congregation, Babat Lamongan. As for the results of this study are: first Mrs. Hj. Yusi Repelitawati, who was born into a Christian family, at the age she was an adult, decided to convert to Islam. He was born into a well-to-do family, but he has a principle that he does not want to trouble his parents until he pioneered his career until he became a successful person and was able to establish a business and a taklim assembly. Mrs. Hj. Yusi lives on Jl. Gotong Royong No. 6 Tripe Lamongan. Second, the feeling of wanting to spread the religion of Islam aroused his enthusiasm to preach to the community, his da'wah strategy by building a taklim assembly while empowering his congregation was well received by the surrounding community even though he was a convert. It has been his goal so that many people can study Islam more broadly, he also wants to help the economy of the congregation of the taklim congregation by empowering the congregation of his taklim congregation into his own business.